PENGARUH VARIASI PRODUK DAN KAPITALISASI BANK TERHADAP FINANCIAL PERFORMANCE DENGAN TEKNOLOGI SEBAGAI VARIABEL MODERASI - Brandon Fernando; Y Agus Bagus Budi N (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2021)
The objective of this.empirical study.is to examine.and to analyze the effect of Product Variety and capitalization of banks on the relation of financial performance, with the usage of internet of things and mobile banking as moderating variables. This research is also used to look further the significance of technology and modernization of the banking sector on its financial success, therefore this research hopefully will inspire and encourage firms in the banking industry to implement and integrate technology into their products line-up. The samples used in this research is the banking sector firms registered in Bursa Efek Indonesia (BEI) and published their annual reports from period of 2017 to 2019. This research uses multiple regression analysis as hypothesis testing method. The result of this empirical study are (1) Product variet dan capitalization of banks do not have positive effect on financial performance. (2) Capitalization of banks have positive and significant effect on financial performance. (3) Internet of things do not moderate positively on the overall of product variety and capitalization of banks. (4) Mobile banking do not moderate positively on the overall of product variety and capitalization of banks.